(untitled) (Lex localis - Journal of Local Self-Government, 2025)
Corporate Social Responsibility (CSR) initiatives on consumer preferences in the organic food sector cannot be overlooked. Consumers nowadays are more aware of their purchasing behavior compared to the past; hence, this research aims to investigate whether consumers prefer brands of companies that participate in CSR activities over those that do not. To achieve the research’s aims, qualitative approaches were employed to capture rich perspectives. A systematic review was conducted using peer-reviewed articles and academic studies available in leading databases. The research findings indicate that health-oriented consumers tend to prefer brands that engage in genuine CSR activities. Additionally, it suggests that CSR enhances customer brand loyalty, improves product quality, and promotes healthy lifestyles. These initiatives highlight the importance of CSR in influencing customer decisions and trust, as well as in enhancing public health, market competitiveness, and overall social well-being.